2015
DOI: 10.1021/acs.jpcc.5b00364
|View full text |Cite
|
Sign up to set email alerts
|

Response of Calcium Carbonate Nanoparticles in Hydrophobic Solvent to Pressure, Temperature, and Water

Abstract: Molecular Dynamics (MD) simulations of surfactant-stabilized calcium carbonate, CaCO 3 , nanoparticles in hydrophobic solvent have been carried out to characterize their response to changes in temperature (T) and pressure (P), and also their interaction with trace water and water droplets. The response to increasing temperature and pressure is sensitive to the type of model surfactant, with the sulfonate-stabilized particle, which is the most spherical, showing a weak temperature-pressure dependence, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The first step is to investigate the relative resistance with respect to diffusion and adsorption based on Eq. (14).…”
Section: Validation Of Mathematical Model Against Mfr Resultsmentioning
confidence: 99%
“…The first step is to investigate the relative resistance with respect to diffusion and adsorption based on Eq. (14).…”
Section: Validation Of Mathematical Model Against Mfr Resultsmentioning
confidence: 99%
“…In the third stage, steered MD and umbrella sampling was used to calculate the free energy of association between two nanoparticles of the same surfactant type, using the same number of species in the OB particle and water as in simulations D to F. The number of each species in the simulations is given in Table . The model nanoparticles in the simulations were performed using the Coulombic annealing and re-forming procedure invented and described in refs .…”
Section: Virtual Experiments Methodologymentioning
confidence: 99%
“…Resolution of this issue reduces to identifying the role that the water interface plays in determining the OB particle shape and also on the effective interaction energy as a function of separation between two OB particles. Our more recent molecular simulation studies have shown that even trace amounts of water interact strongly with the OB calcium carbonate core in the bulk oil. , Therefore, it might reasonably be expected that the effects of surrounding water in the LT experiment arrangement could be significant, although this issue has yet to be fully resolved. This is one of the objectives of this study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations